The global scale and implications of delivering multiple interventions through integrated child health events - Dina Balabanova; Mahoko Kamatsuchi; Adrian Gheorghe (BMJ Global Health)
Introduction Delivering child health services through integrated child health events (ICHEs) has been a useful and popular strategy implemented in many in low-income and middle-income countries (LMICs) to accelerate the reduction of child mortality. The study aims to portray the scope of ICHEs and examine the association between the number of child health-nutrition interventions and types of ICHE packages delivered through these campaigns with vitamin A supplementation (VAS) and measles vaccination.Methods Secondary data analysis was conducted using Unicef global campaign database (1999–2010), where 597 ICHEs from 76 countries were analysed. Panel random effects regression models were used to explore the association between the number of interventions and coverage for VAS and measles vaccination, and non-parametric Kruskal-Wallis test to explore the association between different intervention packages and VAS coverage.Results An average of 100 ICHEs were conducted per year between 2005 and 2010, highest in sub-Saharan Africa (60%). By 2010, 40 ICHEs out of 66 (60%) across 24 countries delivered 5 or more interventions during 1 ICHE. No statistically significant effect of the number of ICHE interventions on VAS coverage was found (−0·76, p=0·185). There was a small significant effect on measles coverage (−1·81, p=0·057), which was not robust to model specifications removing outlier observations with measles coverage lower than 40%. The Kruskal-Wallis test did not suggest a significant association between different intervention packages and VAS coverage at 5% significance level (p=0·07).Conclusion ICHEs were found to be a widely used strategy to deliver essential child health-nutrition interventions in LMICs. ICHEs appear to represent a commonly used platform with the capacity to incorporate multiple interventions without compromising coverage of some key interventions as VAS and measles vaccination. More research is required to better understand what operational factors may affect the coverage outcomes delivered together through ICHEs.